Análise da eficiência do método de extração eletroquímica de íons cloreto para reabilitação de concreto armado com corrosão em região litorânea - Schimelfenig, Beatriz (2022)
By the fact that Brazil has an extensive coastline, it is extremely important to study the interactions between the concrete and the marine environment, in order to prevent pathological manifestations that may arise over time and recover structures damaged by the marine action. In this work, we seek to evaluate the efficiency of the method of electrochemical extraction of chloride ions for the rehabilitation of reinforced concrete with corrosion due to the attack of chlorides in coastal regions. Conducted, in the field, selected as a phenolphthale study and designed in a phenolphthale study by means of Nitrate assay, by means of field spray and designed in the laboratory by X-selection sampling (FRX), Selection diffraction by means of testing performed in the laboratory through X-ray samples (FRX), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Mercury Intrusion Porosimetry. Analysis of the complete concrete analyzes to date, Carbonation, Scanning Electronic Closscopy observe (SEM) it is possible to observe a behavior of the reinforced concrete structure, after the execution, however, it is necessary to comply with too much to fulfill the efficiency of the method, since that are in progress and carried out in the research. Through the proposals made in a concrete way, the application of electrochemistry in concrete in reconstruction and reconstruction of the method tested. Through the analysis of the literature, which affirms the porosity of the analysis of the total porosity of the elaborated set and in accordance with the literature review, which affirms the porosity of the high current resistance used in the electrochemical operation of application methods.